Home Industry Waste Impact Analysis for Environmental Health - Suryani Suryani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Since the beginning of this century, large towns like Bandung have been seeing an increase in the number of environmental issues as a direct result of water pollution caused by residential wastewater generated by their home industries. As a result, there are a great deal of actions that need to be taken in order to solve the problem of water pollution. In Indonesia, a great number of environmental rules and policies have been developed, but the implementation of these policies and regulations has not been carried out to the best of their potential due to a number of flaws in the text of environmental regulations. Developing an ideal policy framework for the administration of wastewater is one potential approach to the problem. Laws governing the management of domestic wastewater must be perfectly supplemented in order to be effective, particularly in the areas of standards, operations and procedures, wastewater quality standards, adequate and quality technology, landscape and building planning, and institutional coordination. This is especially important in large cities. It will be much simpler to implement all of the environmental standards if they are properly synced with one another. The prevention of water pollution will be effectively managed if this practice is followed regularly.